Ruthenium Thrifting – Computation Insights in NH3 Decomposition Onto Ru Single Atom Catalyst CeO2 - Nomcebo P. Motsa; Daniel A. Oduma; Cecil N.M. Ouma; Eni Oko; Michael O. Daramola (Chemical Engineering Transactions)
Noble metals like Ruthenium (Ru) are widely used in various chemical reactions, especially for decomposing ammonia (NH3). NH3 is crucial for the hydrogen economy because it generates hydrogen, a versatile energy source and carrier. However, the high cost and scarcity of noble metals, including Ru, have limited large-scale deployment of NH3 decomposition systems. This study investigates a solution known as noble metal thrifting, which aims to address these challenges. Specifically, it examines the effectiveness of Ru supported on cerium oxide (CeO2) in the form of single-atom catalysts (SACs) using density functional theory (DFT). The obtained results are compared with those of the pristine Ru(111) surface slab. The study observed that NH3 binds more strongly to the Ru SAC system than its decomposition products, N2 and H2. Analysis of the activation energies shows that the dehydrogenation of NH2 is the slowest step in NH3 decomposition over CeO2(111) and pristine Ru(111) catalysts with activation energies of 2.56 eV and 2.26 eV. The initial dehydrogenation of NH3 is the slowest step in the Ru SAC catalyst, with an activation energy of 1.93 eV. The findings from this research are significant because they give credence to the potential of Ru thrifting, particularly Ru SAC supported on CeO2, as a probable means to utilize the efficacy of Ru in the decomposition of NH3, without the limitations associated with noble metal scarcity and cost.